2012
DOI: 10.1039/c2fo30038a
|View full text |Cite
|
Sign up to set email alerts
|

In depth study of acrylamide formation in coffee during roasting: role of sucrose decomposition and lipid oxidation

Abstract: Coffee, as a source of acrylamide, needs to be investigated in depth to understand the contribution of different precursors. This study aimed to investigate the contributions of sucrose decomposition and lipid oxidation on acrylamide formation in coffee during roasting. Coffee beans and model systems were used to monitor the accumulation of neo-formed carbonyls during heating through sucrose decomposition and lipid oxidation. High resolution mass spectrometry analyses confirmed the formation of 5-hydroxymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 22 publications
2
60
0
Order By: Relevance
“…Thirdly, CGA retarded HMF elimination during heating, especially in the Maillard reaction system. Moreover, during the drying process of fruits, CGA may also increase HMF formation by catalysing the decomposition of sucrose to fructose, as found by Kocadagh et al (2012) during the toasting of coffee.…”
Section: Catalytic Capacity Of Other Phenol Compounds and The Analogumentioning
confidence: 97%
See 1 more Smart Citation
“…Thirdly, CGA retarded HMF elimination during heating, especially in the Maillard reaction system. Moreover, during the drying process of fruits, CGA may also increase HMF formation by catalysing the decomposition of sucrose to fructose, as found by Kocadagh et al (2012) during the toasting of coffee.…”
Section: Catalytic Capacity Of Other Phenol Compounds and The Analogumentioning
confidence: 97%
“…A high HMF content in coffee, dried plum and pear, amounting to 4100, 3200 and 3500 mg/kg, respectively has been reported (Bachmann, Meier, & Kanzig, 1997;Capuano & Fogliano, 2011); suggesting that CGA may contribute to HMF formation. Kocadagh, Goncuoglu, Hamzalhoglu, and Gokmen (2012) found that, during high-temperature treatment (180°C), CGA increased the hydrolysis of sucrose to form fructose, which may contribute to the high content of HMF in coffee. However, whether CGA has alternative mechanisms to influence HMF formation, such as promoting the direct conversion of hexose to HMF, is unknown.…”
Section: Introductionmentioning
confidence: 97%
“…To the best of our knowledge, a few studies specifically deal with the mechanisms of acrylamide formation in coffee and coffee substitutes [13][14][15]. Nevertheless, more than one route of generation of the toxic molecules have been suggested [16].…”
Section: Mechanisms Of Acrylamide Formation In Coffee and Coffee Subsmentioning
confidence: 99%
“…Although Granvogl et al [25] demonstrated that the 3-APA is an efficient precursor of acrylamide in model systems and potatoes, where it can be generated also through the biochemical decarboxylation of asparagine, it was neither detected in raw nor in roasted coffee [13]. It has been recently suggested that 5-hydroxymethylfurfural (HMF), which is also generated during roasting, could play a role in acrylamide formation [14,15]. It has been recently suggested that 5-hydroxymethylfurfural (HMF), which is also generated during roasting, could play a role in acrylamide formation [14,15].…”
Section: Mechanisms Of Acrylamide Formation In Coffee and Coffee Subsmentioning
confidence: 99%
“…There are other factors rather than antioxidant structure, which can affect acrylamide content. For example, some phenolic acids like chlorogenic acid can convert sucrose into more reactive intermediates like 5-Hydroxymethylfurfural that reacts with aspargine with more tendency, and increases acrylamide production (Kocadagl et al 2012). On the other hand, some flavonoids like naringenin or epicatechin decrease acrylamide production through reaction with different intermediates of Maillard reaction and trapping them Totlani and Peterson 2005;Totlani and Peterson 2006).…”
Section: Reduction Of Acrylamide Content In Foodsmentioning
confidence: 99%